PENGARUH BUDAYA LOKAL TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SUNGAI PENUH - Dedi Afrison (EDU RESEARCH, 2023)
This article aims to examine the influence of local culture on Islamic Religious Education learning in Sungai Penuh. Sungai Penuh, which is rich in the traditions and cultural values of its people, offers a unique context for the implementation of religious education. This research uses a qualitative approach with interview and observation methods with educators and students in several educational institutions, including madrasah and public schools. The results show that local culture plays a significant role in enriching teaching materials and learning methods. The integration of cultural values, such as mutual cooperation, respect for parents, and local wisdom, is proven to increase students' motivation in understanding Islamic teachings. In addition, the use of local languages in teaching also helps students to more easily grasp the religious concepts taught. However, there is a challenge in balancing the sometimes conflicting teachings of religion and local culture. Therefore, it is important for educators to develop a curriculum that is sensitive to local culture without compromising the values of Islamic teachings. This research is expected to contribute to the development of a more relevant and contextualized religious education in Sungai Penuh, as well as a reference for researchers and educators in an effort to improve the quality of Islamic Religious Education learning.